Crop geometry and nutrient (N-P-K-S) management for kharif onion bulb (Allium cepa) crop - BHARDWAJ, RAJU LAL; PARASHAR, AABHA (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during rainy (kharif) seasons of 2020 and 2021 at College of Agriculture (Agriculture University, Jodhpur, Rajasthan), Sumerpur, Pali, Rajasthan to find out the optimal quantity of N-P-K-S nutrients and appropriate crop geometry to maximize the productivity and bulb quality of onion (Allium cepa L.). The experiment was conducted in split-plot design (SPD) by means of 3 levels of N-P-K-S nutrients in main plots and 5 crop geometries under sub-plot, replicated thrice. Widest crop geometry (15 cm × 15 cm) with highest level of nutrients (140 N-80 P-80 K-40 S) resulted in highest tallness of plant (97.8 cm), maximum leaves (19/plant), root length (9.9 cm), number of roots/plant (139.8), average bulb weight (133.9 g) and harvest index (51.2). Saleable bulbs (43.6 t/ ha), total income (6753.8 USD), net income (5462.6 USD) and Benefit: cost (B:C) ratio (4.23) was the highest in 10 cm × 10 cm geometry with highest level of N-P-K-S nutrients. Maximum biological production (125.8 t/ha), bulb production (61.8 t/ha) was observed at closest geometry (7.5 cm × 7.5 cm) with highest level of N-P-K-S nutrients. It was confirmed by experimentation, that the onion seedling should be transplanted at 10 cm × 10 cm geometry with 140 N-80 P-80 K-40 S kg/ha nutrients in medium fertile sandy loam soil in arid agro-climatic condition for maximum saleable good quality onion bulbs production.